2007
DOI: 10.1890/05-1963
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Legacies in Forest Environments: Tree Communities, Soil Properties, and Light Availability

Abstract: Temperate deciduous forests across much of Europe and eastern North America reflect legacies of past land use, particularly in the diversity and composition of plant communities. Intense disturbances, such as clearing forests for agriculture, may cause persistent environmental changes that continue to shape vegetation patterns as landscapes recover. We assessed the long-term consequences of agriculture for environmental conditions in central New York forests, including tree community structure and composition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
137
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(146 citation statements)
references
References 50 publications
6
137
2
1
Order By: Relevance
“…Forests were cleared for agricultural use, and after abandonment, succession led to the establishment of secondary forests. Consistent with results from this study, others have demonstrated that during succession from abandonment of agricultural fields to forests, carbon increases (Brunet et al, 2012;DeGryze et al, 2004;Falkengren-Grerup et al, 2006;Flinn and Marks, 2007), pH decreases (Falkengren-Grerup et al, 2006;Schrijver et al, 2012) and the C:N ratio increases (Compton and Boone, 2000). The young soils at the SERC stands were less acidic and contained less Al compared to the old forest soils in both the surface and lower depths.…”
Section: Soil Chemical Propertiessupporting
confidence: 91%
“…Forests were cleared for agricultural use, and after abandonment, succession led to the establishment of secondary forests. Consistent with results from this study, others have demonstrated that during succession from abandonment of agricultural fields to forests, carbon increases (Brunet et al, 2012;DeGryze et al, 2004;Falkengren-Grerup et al, 2006;Flinn and Marks, 2007), pH decreases (Falkengren-Grerup et al, 2006;Schrijver et al, 2012) and the C:N ratio increases (Compton and Boone, 2000). The young soils at the SERC stands were less acidic and contained less Al compared to the old forest soils in both the surface and lower depths.…”
Section: Soil Chemical Propertiessupporting
confidence: 91%
“…Intensive anthropogenic disturbances, such as agriculture, often strongly reduce resource heterogeneity and b-diversity of plants and animals (Robertson et al 1993;Flinn and Marks 2007;Karp et al 2012). In turn, studies documenting natural forest recovery show that heterogeneity of habitat structure and species distributions increase over time (Denslow and Guzman 2000;Guariguata and Ostertag 2001;Cook et al 2005), but still are often lower in older secondary forests than in primary forests (Nicotra et al 1999;Flinn and Marks 2007). Restoration efforts across a range of systems have often failed to restore heterogeneity of abiotic conditions and community composition approaching that of more intact systems (Holl 2002b;Polley et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…There is ample evidence of persistent (a)biotic differences between post-agricultural stands and forest stands for which there is no historical record of alternative land use ('ancient forest'). The abiotic legacies of former land use are expressed in soil nutrient availability (e.g., Koerner et al 1997;Verheyen et al 1999;Falkengren-Grerup et al 2006) and spatial heterogeneity of soil properties (Fraterrigo et al 2005;Flinn and Marks 2007). Among other nutrients, phosphorus (P) has specifically drawn the attention.…”
Section: Introductionmentioning
confidence: 99%